1999
DOI: 10.1080/00034989957745
|View full text |Cite
|
Sign up to set email alerts
|

Malaria in pregnancy: its relevance to safe-motherhood programmes

Abstract: Severe anaemia in pregnancy is an important contributor to maternal and perinatal morbidity and mortality. In sub-Saharan Africa severe anaemia in pregnancy is very common, the main causes being iron and folate deficiency, malaria, hookworm infestation and advanced HIV infection. Though most of these causes are preventable, the overall prevalence of anaemia has not changed over many years. This is probably due to a mixture of reasons, including operational problems and inadequate interventions. In addition, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 27 publications
(16 reference statements)
0
19
0
1
Order By: Relevance
“…Self-medication was preferred among the general population, but was practiced more amongst residents of Kaneshie. Shulman 14 observed that self-medication has become popular as a result of the creation of awareness through education on home management and control of malaria. During this study, we observed that people from both sites had adequate information on home management of malaria, especially through awareness programs organised through the media.…”
Section: Discussionmentioning
confidence: 99%
“…Self-medication was preferred among the general population, but was practiced more amongst residents of Kaneshie. Shulman 14 observed that self-medication has become popular as a result of the creation of awareness through education on home management and control of malaria. During this study, we observed that people from both sites had adequate information on home management of malaria, especially through awareness programs organised through the media.…”
Section: Discussionmentioning
confidence: 99%
“…83 There is also good evidence that severe anemia increases the risk of maternal mortality. 2 If one assumes a maternal mortality ratio for sub-Saharan Africa (excluding southern Africa) of 1,000 per 100,000 live births), 84 and if one assumes that between 8% and 20% of these deaths are caused by severe anemia, 2 this would translate to up to 10,000 malarial anemia-related deaths per year.…”
Section: Discussionmentioning
confidence: 99%
“…These lacunae have hampered effective lobbying for the inclusion of malaria prevention in the new Safe Motherhood Initiatives. 2 This article reviews the available evidence on the coincidental risks of anemia and malaria among pregnant women in sub-Saharan Africa.…”
Section: Introductionmentioning
confidence: 99%
“…The Kenyan Ministry of Health introduced national guidelines for the control of malaria in pregnancy, which included the use of intermittent preventive treatment with SP in 1999, after this study was completed. 4 Study design and randomization. This study was conducted within the context of a large community based group randomized controlled trial designed to assess the impact of ITNs on mortality in children less than five years of age.…”
Section: Methodsmentioning
confidence: 99%
“…1,2 In areas with stable malaria transmission, which represents most of sub-Saharan Africa, the vast majority of infections with Plasmodium falciparum in pregnancy remain asymptomatic, undetected and untreated. 3,4 The major impact of malaria during pregnancy in these regions is caused by persistent or recurrent, predominantly lowgrade, sometimes sub-patent [5][6][7] parasitemia, resulting in maternal anemia and a reduced birth weight. 8 Primigravidae and secundigravidae are most at risk, but in areas with moderateto-intense transmission, or a high prevalence of infection with human immunodeficiency virus (HIV), women of higher gravidity are also affected.…”
Section: Introductionmentioning
confidence: 99%